Microalgal feedstock for bioenergy: Opportunities and challenges - Reis, Cristiano Eduardo Rodrigues; De Souza Amaral, Mateus; Loures, Carla Cristina Almeida [UNESP]; Da Rós, Patrícia Caroline Molgero; Hu, Bo; Filho, Hélcio José Izário; De Castro, Heizir Ferreira; Gianesella, Sônia Maria Flores; Silva, Messias Borges [UNESP] (Springer Nature, 2014)
The utilization of algal feedstock for bioenergy can be considered as one of the greatest challenges for biosystems engineering in the near future. Some species of microalgae show high potential for oil accumulation and further utilization of its biomass for biogas generation, pyrolysis, ethanol production, and even as fertilizer. Microalgae can utilize CO2 as carbon source and can also be grown on nonagricultural environments, such as wastewater facilities, industrial effluents, freshwater, and marine water habitats. The vast research field on microalgae engineering is due to the facts that it can be a source of energy and act as an air and water pollutants removal. There have been considerable advances in engineering its growth, in bioreactor designs, and on lipid accumulation due to chemical, biochemical, and genetic studies. Despite that, there are still some fundamental processing aspects that are considered challenges, either economical, ecological, or technical, such as biomass harvesting and the competition with the higher value products produced from algae, as proteins.